ЗАСТОСУВАННЯ КРІОГЕННИХ ТЕХНОЛОГІЙ У КОМПЛЕКСНОМУ ЛІКУВАННІ АДЕНОКАРЦИНОМИ ЖОВЧНОГО МІХУРА З ІНВАЗІЄЮ В ГІЛКИ ВОРІТНОЇ ВЕНИ: КЛІНІЧНИЙ ВИПАДОК - Dronov, O.; Kozachuk, Y.; Bakunets, Y.; Bakunets, P.; Prytkov, F. (PH Akademperiodyka, 2023)
The right trisectionectomy is the main treatment modality for locally advanced gallbladder cancer with invasion of the intraparenchymal portal vein branches because it allows the achievement of negative resection margins (R0). However, only 10%—25% of such patients are eligible for surgery. The cryosurgical method has been successfully used in the complex treatment of hepatopancreatobiliary malignant neoplasms for many years. The possibility of its application close to major blood vessels is one of its advantages. In the presented case, the cryodestruction of the residual tumor with invasion into the anterior wall of the left branch of the portal vein was used as a debulking option during liver resection (R2) due to locally advanced gallbladder cancer. The cryodestruction was performed with application method with a double cryocycle and spontaneous thawing using a Cryo-Pulse device and liquid nitrogen as a cryoagent. No postoperative complications related to cryodestruction were noted. The cryogenic technologies application in the debulking surgery of gallbladder cancer can be a safe treatment modality for residual tumors with invasion into the intraparenchymal branches of the portal vein.